Proceedings Of The 18th Annual Meeting Of The Asia Oceania Geosciences Society (Aogs 2021) Singapore, 01 - 06 August 2021 - Van Thanh, Nguyen; Liong, Shie-Yui; Satoh, Masaki (World Scientific Publishing Company, 2022)
The 18th Annual Meeting of the Asia Oceania Geosciences Society (AOGS 2021) was held from 1st to 6th August 2021. This proceedings volume includes selected extended abstracts from a challenging array of presentations at this conference. The AOGS Annual Meeting is a leading venue for professional interaction among researchers and practitioners, covering diverse disciplines of geosciences.